2014
DOI: 10.1177/1468087414530965
|View full text |Cite
|
Sign up to set email alerts
|

Overview of the main mechanisms triggering low-speed pre-ignition in spark-ignition engines

Abstract: Low-speed pre-ignition has become of great concern since it represents a strong limit to any further downsizing of gasoline engines. The increase of pressure and temperature inside the combustion chamber at high loads can indeed lead to a premature auto-ignition of the mixture and to severe engine damages. Several hypotheses have been formulated but there is no consensus to explain and demonstrate the cause of low-speed pre-ignition. This article provides an overview of the mechanisms that might lead to low-sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(29 citation statements)
references
References 39 publications
2
27
0
Order By: Relevance
“…Because gasoline dilution reduces the viscosity and surface tension of the oil, the droplet is likely to be released from the crevice because of the inertial forces during deceleration of the piston just before it reaches TDC. Currently, this explanation regarding the ingress of oil into the combustion chamber is widely accepted [72,75]. The release of oil droplets from the piston crevice at the end of the compression stroke has also been observed by Kassai et al [76] Lauer et al [77] confirmed that pre-ignition frequently leads to follow-up events.…”
Section: Pre-ignition-sourcessupporting
confidence: 52%
See 3 more Smart Citations
“…Because gasoline dilution reduces the viscosity and surface tension of the oil, the droplet is likely to be released from the crevice because of the inertial forces during deceleration of the piston just before it reaches TDC. Currently, this explanation regarding the ingress of oil into the combustion chamber is widely accepted [72,75]. The release of oil droplets from the piston crevice at the end of the compression stroke has also been observed by Kassai et al [76] Lauer et al [77] confirmed that pre-ignition frequently leads to follow-up events.…”
Section: Pre-ignition-sourcessupporting
confidence: 52%
“…Fuel composition and properties have been shown to have a relatively large impact on the frequency of pre-ignition occurrence [75,[96][97][98][99]. It is clearly evident and well established that aromatic content has a large positive correlation with the pre-ignition frequency [96,99], although the associated mechanism is not well understood.…”
Section: Fuel Propertiesmentioning
confidence: 98%
See 2 more Smart Citations
“…Super knock usually happens before the spark ignition, which drives researchers to relate it to pre-ignition. Therefore, endeavors were made to dig the cause of pre-ignition [1][2][3][4]. On the other hand, although preignition is reckoned to be the indicator, it actually doesn't necessarily result in super knock.…”
Section: Introductionmentioning
confidence: 99%